The Profile of The First Women Presenting for Elective Termination of Pregnancy at the Pretoria Academic Hospital - R.E. Kirby; J.J. Blitz; T. McD Kluyts (South African Family Practice)
Introduction: At the time of the study (1998), a termination of pregnancy, (TOP) service had never been provided at Pretoria Academic Hospital or elsewhere in South Africa before and this elicited much speculation about the women who would present for this service. It was decided to study the first group of women who came to Pretoria Academic Hospital for this service and explore some of the issues surrounding their decision.